Mixed control scheme for accurate control of robotic flexible endoscope. (4th April 2017) - Zhang, Aoyu; Han, Zhimin; Wang, Xiguang; Briggs, Randall; Xie, Tianyu
Tendon-driven endoscopes are mainly used in the current practice. Their flexible bodies may change frequently during the processes of biopsy, endoscopic mucosal resection or endoscopic submucosal dissection. These changes lead to backlash hysteresis and nonlinear friction effects, which make it difficult to achieve accurate control. To address this problem, a mixed control scheme based on the combination of discrete and continuous models was proposed and quantitatively compared with a conventional feedback control scheme, a feedforward control scheme and an adaptive control scheme. These experiments were conducted using a robotic gastroscope. The results showed that our control scheme can achieve more accurate tracking performance when the configuration changes frequently, with mean square error of tracking performance decreased by 50–75%.